Chronic stress from adolescence to adulthood increases adiposity and anxiety in rats with decreased expression of Krtcap3 - Szalanczy, Alexandria M.; Fitzpatrick, Mackenzie; Beeson, Angela; Bui, Trangdai; Dyson, Christina; Eller, Seth; Landry, Julia; Scott, Christina; Grzybowski, Michael; Klotz, Jason; Geurts, Aron M.; Weiner, Jeff L.; et al. (Frontiers in Genetics, 2024)
During the COVID-19 pandemic, there was an alarming increase in obesity that corresponded to an increase in stress, highlighting the connection between stress and obesity that is rarely incorporated into obesity research. In our own previous work, changes in environmental stressnoise due to COVID-19 shutdowns suggestedrevealed that the relationship between Krtcap3 and obesity in rats may depend on stress. In the current study, we confirmed Krtcap3 as a stress response gene with downstream effects on adiposity and behavior. We found that Krtcap3-KO rats had increased adiposity and anxiety-like behaviors following chronic stress, while there were minimal differences in the WT rats. We further demonstrate that stress altered expression levels of the glucocorticoid receptor, Nr3c1, in both the pituitary and colon of KO rats, with no changes in WT rats. These data support the role of Krtcap3 in the stress response, potentially through interactions with Nr3c1. This work also validates the importance of accounting for environmental stress in genetic research in both animal models and humans.